On the gender–science stereotypes held by scientists: explicit accord with gender-ratios, implicit accord with scientific identity - Smyth, Frederick L.; Nosek, Brian A. (Frontiers in Psychology, 2015)
Women’s representation in science has changed substantially, but unevenly, over the past 40 years. In health and biological sciences, for example, women’s representation among U.S. scientists is now on par with or greater than men’s, while in physical sciences and engineering they remain a clear minority. We investigated whether variation in proportions of women in scientific disciplines is related to differing levels of male-favoring explicit or implicit stereotypes held by students and scientists in each discipline. We hypothesized that science-is-male stereotypes would be weaker in disciplines where women are better represented. This prediction was tested with a sample of 176,935 college-educated participants (70% female), including thousands of engineers, physicians, and scientists. The prediction was supported for the explicit stereotype, but not for the implicit stereotype. Implicit stereotype strength did not correspond with disciplines’ gender ratios, but, rather, correlated with two indicators of disciplines’ scientific intensity, positively for men and negatively for women. From age 18 on, women who majored or worked in disciplines perceived as more scientific had substantially weaker science-is-male stereotypes than did men in the same disciplines, with gender differences larger than 0.8 standard deviations in the most scientifically-perceived disciplines. Further, particularly for women, differences in the strength of implicit stereotypes across scientific disciplines corresponded with the strength of scientific values held by women in the disciplines. These results are discussed in the context of dual process theory of mental operation and balanced identity theory. The findings point to the need for longitudinal study of the factors’ affecting development of adults’ and, especially, children’s implicit gender stereotypes and scientific identity.